The Role of Gangubai as a Surrogate Mother in Sanjay Leela Bhansali's Gangubai Kathiawadi - Dinurriyah, Itsna Syahadatud (Pusat Studi Gender Universitas Jember, 2024)
This research aims to examine Gangubai’s role as a surrogate mother in the brothel of Kamathipura. A surrogate mother is crucial in the prostitution area since the sex workers do not have any access to law, education, or health facilities. They even are threatened with being homeless. Thus, Gangu’s emergence as the leader in the brothel saves the prostitutes there. She is chosen by her friends in the brothel as the one who can protect their lives. Gangu is a well-educated girl from a prominent family in Kathiawar. Her father is a well-known lawyer. Therefore, she is the one who advocates for women who work in the prostitution area in Kamathipura. Like her, women who are trapped as sex workers are those who are deceived by the ones they love. Gangu turns out to be a sex worker after her boyfriend, Ramnik, manipulated her to be a film star. This research is a qualitative one that explores the analysis through textual critical description. This research employs the feminist-rational choice approach that emphasizes female liberation on gender, strategy, institutions, power, and change. To get the findings, this research focuses on two themes that are the idea of a surrogate mother in the brothel and how the surrogate mother implements her power to protect her workers in her place.